2015
DOI: 10.1136/bmj.h1703
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, geographical, and temporal risk factors associated with presentation and outcome of vivax malaria imported into the United Kingdom over 27 years: observational study

Abstract: ObjeCtiveTo examine temporal and geographical trends, risk factors, and seasonality of imported vivax malaria in the United Kingdom to inform clinical advice and policy. DesignObservational study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 34 publications
1
29
1
1
Order By: Relevance
“…It has been argued before that the malaria risk for travellers is not correlated with infection rates in the local population and attack rates in visitors may likely be higher because of the absence of partial immunity in contrast to the local populations [33]. Recent studies confirmed the trend of decreasing cases of imported malaria cases from SEA [9, 34]. According to data from malaria surveillance reports from the USA and 12 European countries, malaria cases imported from countries of SEA declined by 47% between 2003 and 2008 [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been argued before that the malaria risk for travellers is not correlated with infection rates in the local population and attack rates in visitors may likely be higher because of the absence of partial immunity in contrast to the local populations [33]. Recent studies confirmed the trend of decreasing cases of imported malaria cases from SEA [9, 34]. According to data from malaria surveillance reports from the USA and 12 European countries, malaria cases imported from countries of SEA declined by 47% between 2003 and 2008 [8].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, numbers of travellers to those regions have increased substantially due to a major surge in the availability of flight connections as well as a dramatic decrease in airline fares [7]. Concurrently to increased travel, malaria transmission in most parts of SEA has decreased, resulting in smaller numbers of imported malaria from the region [8, 9]. India also recorded a decline in malaria cases, but predominantly through control of falciparum malaria.…”
Section: Introductionmentioning
confidence: 99%
“…Since wild chimpanzees in West and Central Africa were confirmed hosts of P. vivax-like strains, it was hypothesised that wild apes could act as a natural reservoir (Rayner et al, 2011), thereby explaining the occasional infection of travellers despite the low prevalence of P. vivax in the human populations of these regions (Broderick et al, 2015;Culleton et al, 2008;Gautret et al, 2001;Mühlberger et al, 2004;Skarbinski et al, 2006). Moreover, a P. vivax-like parasite isolated from a traveller coming back from a Central African forest was recently shown to cluster with the AGA isolates outside of the human lineage, confirming the occurrence of cross-species transmissions (Liu et al, 2014;Prugnolle et al, 2013).…”
Section: Interspecies Transmissionmentioning
confidence: 99%
“…However, P. falciparum malaria importation from endemic regions and the threat of spreading drug resistance remains a problem for many eliminating or malaria-free countries due to the difficulty of diagnosis, substantial burden of treatment, relatively high mortality rates, and potential secondary local transmission67. The importation of malaria from Africa has been common over the past decades in non-endemic countries such as the UK and France, that have historical, language and cultural ties89, and certain demographic groups exhibit substantially higher infection rates, such travellers visiting friends and relatives in endemic countries71011.…”
mentioning
confidence: 99%